2020
DOI: 10.1051/0004-6361/202038116
|View full text |Cite
|
Sign up to set email alerts
|

Carbon monoxide formation and cooling in supernovae

Abstract: Context. The inclusion of molecular physics is an important piece that tends to be missing from the puzzle when modeling the spectra of supernovae (SNe). Molecules have both a direct impact on the spectra, particularly in the infrared, and an indirect one as a result of their influence on certain physical conditions, such as temperature. Aims. In this paper, we aim to investigate molecular formation and non-local thermodynamic equilibrium (NLTE) cooling, with a particular focus on CO, the most commonly detecte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(50 citation statements)
references
References 76 publications
3
47
0
Order By: Relevance
“…CO fundamental (day 117) and first overtone emission (day 112) was first detected in SN 1987A by Spyromilio et al (1988). Modeling by these authors suggested a CO mass of about 5 × 10 −5 M at day 285, while Liljegren et al (2020) estimated a much larger mass of 4 × 10 −3 M . Because of the reduction in temperature in the C/O region, Liljegren et al (2020) indicates that the O/C region will not be a significant contribution to the [O I] λλ 6300, 6364 in the optical region.…”
Section: O I Emissionmentioning
confidence: 95%
See 1 more Smart Citation
“…CO fundamental (day 117) and first overtone emission (day 112) was first detected in SN 1987A by Spyromilio et al (1988). Modeling by these authors suggested a CO mass of about 5 × 10 −5 M at day 285, while Liljegren et al (2020) estimated a much larger mass of 4 × 10 −3 M . Because of the reduction in temperature in the C/O region, Liljegren et al (2020) indicates that the O/C region will not be a significant contribution to the [O I] λλ 6300, 6364 in the optical region.…”
Section: O I Emissionmentioning
confidence: 95%
“…Modeling by these authors suggested a CO mass of about 5 × 10 −5 M at day 285, while Liljegren et al (2020) estimated a much larger mass of 4 × 10 −3 M . Because of the reduction in temperature in the C/O region, Liljegren et al (2020) indicates that the O/C region will not be a significant contribution to the [O I] λλ 6300, 6364 in the optical region. SiO was also present from ∼160 d, with an estimated mass of about 4 ± 2 × 10 −6 M near day 500 (Roche et al 1991).…”
Section: O I Emissionmentioning
confidence: 98%
“…the carbon monoxide (CO) features in the K-band region) and is crucial to investigate dust formation (Morgan & Edmunds 2003). Due to the large number of collisionally excitable energy levels of CO emission, it acts as a coolant and can shed light on the dust production rate in SN ejecta (Gearhart, Wheeler & Swartz 1999;Morgan & Edmunds 2003;Liljegren, Jerkstrand & Grumer 2020). The NIR spectra of SNe Ib exhibit strong features of He I λ10 800 and C I, which give an idea about the extent of envelope stripping in these objects.…”
Section: Introductionmentioning
confidence: 99%
“…Both from the observed strength of the molecular emission (e.g. Meikle et al 1989;Kotak 2009), and the only two studies calculating molecular cooling so far (Liu & Dalgarno 1995;Liljegren et al 2020) molecules appear capable of cooling the ejecta significantly, perhaps by several thousand degrees. This would strongly affect the optical spectrum which for many SNe is the only spectral region observed.…”
Section: Introductionmentioning
confidence: 99%